Identifikasi Akuifer Air Tanah Dalam Menggununakan Metode Geolistrik Schlumberger di Desa Wedomartani, Kabupaten Sleman - Muhammad Faizal Zakaria (Fakultas Teknologi Mineral, Universitas Pembangunan Nasional (UPN), 2019)
Water is the main problem in every region that has a rapid population increase, one of which is Wedomartani village, Sleman Regency. This study aims to determine the water reserves in Wedomartani village and find out the direction of groundwater flow in the area. The research carried out by measuring geolectricity method (Schlumberger configuration) survey of 15 very point acquisition with an average stretch of 250 m. The tool used in geoelectric measurement is Resistivity Meter Syscal Jr. The software used in processing is Progress 3.0. The results of data processing is resistivity variations function of depth per point acquisition that will interpreted into rock types and water content. The average resistivity of groundwater aquifers in Wedomartani village is 19.49 Ωm and the average depth of groundwater aquifers in Wedomartani village is 101 m. The direction of deep groundwater flow in Wedomartani village generally leads from north to south and west (in the southern part of the research area.